Gestational hypertensive disease in twin pregnancy: Influence on outcomes in a large national prospective cohort. (15th June 2016) - Hehir, Mark P.; Breathnach, Fionnuala M.; McAuliffe, Fionnuala M.; Geary, Michael P.; Daly, Sean; Higgins, John; Hunter, Alyson; Morrison, John J.; Burke, Gerard; Higgins, Shane; Mahony, Rhona; Dicker, Patrick; et al.
Abstract : Objective: Gestational hypertensive disease (GHD) is associated with pregnancy‐related complications and poor maternal and fetal outcomes in singleton pregnancies. We sought to examine the influence of GHD in a large prospective cohort of twin pregnancies. Study design: The ESPRIT study was a national multicenter observational cohort study of 1028 structurally normal twin pregnancies. Each pregnancy underwent sonographic surveillance with two‐week ultrasound from 24 weeks for dichorionic and from 16 weeks for monochorionic gestations. Characteristics and demographics as well as labour and delivery outcome data were prospectively recorded. Perinatal mortality, admission to the neonatal intensive care unit (NICU) and a composite of morbidity of respiratory distress syndrome, hypoxic ischaemic encephalopathy, periventricular leukomalacia, necrotising enterocolitis and sepsis were documented for all cases. Outcomes for patients with documented GHD (pre‐eclampsia and gestational hypertension) were compared with those without GHD. Results: Perinatal outcome data were recorded for 977 patients. Women with GHD had a higher body mass index (27.1 ± 6.4 vs 25.2 ± 4.5, P < 0.0001) than those without and were more likely to be nulliparous (65% (59/92) vs 46% (407/885), P = 0.001). Both groups had similar mean birthweights, but those with GHD were more likely to have a birthweight discordance ≥18% (35% (32/92) vs 20% (179/885), P = 0.001). Rates of caesarean delivery were higher in those twin pregnancies affected by GHD, and while the rate of composite morbidity was similar in both groups, twins in the GHD group had higher rates of NICU admission. Conclusion: In twin gestations, gestational hypertension independently confers an increased risk for emergency caesarean delivery, birthweight discordance and NICU admission, such that intensive maternal–fetal monitoring is justified when hypertension develops in a twin pregnancy.